The spell-out algorithm and lexicalization patterns Slavic verbs and complementizers - Wiland, Bartosz (Language Science Press, 2019)
The book covers the morphosyntax of verbs and categories syncretic with the declarative complementizer in Slavic, together with a comparative look at the similar categories in Latvian (Baltic) and Basaá (Bantu). In the domain of verbs, the book investigates an analytic vs. fusional realization of grammatical categories that we find in a semelfactive-iterative alternation in Czech and Polish, where a semelfactive verb stem such as in the Czech kop-n-ou-t 'give a kick' alternates with an iterative verb stem as in kop-a-t 'kick repeatedly'. The iterative -aj stem is morphologically less complex than the semelfactive stem formed with the -n-ou sequence, which is paradoxical given syn-sem representation is more complex than semelfactives. In the domain of complementizers, the book focuses on cross-categorial paradigms that include an unexpected morphological containment (in Russian), a degree of morphological complexity (in Latvian), and an ABA pattern of syncretic alignment (in Basaá).